Kinetic analyses for solid-state phase transition of metastable amorphous-AlOx (2.5 < x ≤ 3.0) nanostructures into crystalline alumina polymorphs - Elijah M. Davis; Claudia Rawn; Matthew G. Boebinger; Dibyendu Mukherjee (Scientific Reports)
Abstract Solid-solid phase change materials (SS-PCMs) hold promise for energy storage/dissipation in batteries and energetic materials. Yet, phase change kinetics for SS-PCMs undergoing metastable to semi-stable/stable phase transformations remain relatively ill-studied because trapping metastable phases remain challenging. Recently, we demonstrated the kinetic entrapment and stabilization of a highly disordered and amorphous Al-oxide phase m-AlOx@C (x~2.5-3.0) via laser ablation synthesis in solution (LASiS). We report here, to our knowledge, the first chemical kinetics analysis for S-S phase transition of the m-AlO3@C nanocomposites (< 5–8 nm sizes) into semi-stable equilibrium alumina phases (θ/γ-Al2O3) via disproportionation reaction, while releasing excess trapped gases. Our results indicate the atomic density of the AlO3 structures to be ~5–10 times less than that of the final Al2O3 phases, which led to the hypothesis of a volume shrinkage process during their phase transition. Temperature-dependent X-ray diffraction studies reveal the high-temperature phase transition for m-AlO3 → θ/γ-Al2O3 to follow contracting volume kinetics model, thereby validating our earlier hypothesis. Using the geometric volume contraction model, reaction kinetics analyses from Arrhenius plots reveal the activation energy barrier for the phase transition to be ~270±11 kJ/mol. This makes the activation energy barrier nearly identical to the oxidation of micron-sized Al particles.